Is the risk of contrast-induced nephropathy a real contraindication to perform intravenous contrast enhanced Computed Tomography for non-traumatic acute abdomen in Emergency Surgery Department? - De Simone, Belinda; Ansaloni, Luca; Sartelli, Massimo; Gaiani, Federica; Leandro, Gioacchino; de' Angelis, Gian Luigi; Di Mario, Francesco; Coccolini, Federico; Catena, Fausto (Acta Biomedica Atenei Parmensis, 2018)
Background: Contrast enhanced Computed Tomography (CCT) is the most used imaging test to investigate acute abdominal clinical conditions, because of its high sensitivity and specificity. It is mandatory to make a correct and prompt diagnosis when life threatening abdominal diseases as mesenteric ischemia are suspected. Contrast medium administration was linked to acute renal failure, therefore radiologist often prefer to perform CCT without contrast in patients needing to undergo the exam with increased serum creatinine.  The aim of the review was to focus on the incidence of contrast induced nephropathy in patients presenting non-traumatic acute abdominal clinical conditions, who underwent CCT with intravenous contrast agent administration in emergency setting. Materials and Methods: The systematic review protocol was guided by the Preferred Reporting Items for Systematic Reviews and Meta-analyses Protocol (PRISMA-P). Quality of the evidence will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. Results: The strongest currently available evidence on the incidence of post-contrast acute kidney injury (AKI) following intravenous contrast agent administration consists in a meta-analysis of observational studies. Data extracted from meta-analyses demonstrate that, compared with non-contrast CT, CCT was not significantly associated with AKI. Moreover, the risk of AKI (RR=0.79; 95% confidence interval [CI]: 0.62, 1.02; P=.07), death (RR=0.95; 95% CI: 0.55, 1.67; P=.87), and dialysis (RR=0.88; 95% CI: 0.23, 3.43; P=.85) is similar, compared with the risk of AKI in the non-contrast medium group. Furthermore, intravenous low-osmolality iodinated contrast material is a nephrotoxic risk factor, but not in patients with a stable SCr level less than 1.5 mg/dL, therefore many factors other than contrast material could affect PC-AKI rates. Discussion and conclusions: The benefits of diagnostic information gained from contrast enhanced TC in assessing AA are fundamental in some clinical scenarios. The risk of contrast induced nephropathy (CIN) is negligible in patients with normal renal function but the incidence appears to rise to as high as 25% in patients with pre-existing renal impairment or in the presence of risk factors such as diabetes, advanced age, vascular disease and use of certain concurrent medications. The incidence of CIN/AKI after intravenous contrast administration is very low in general population. Radiologists and referring physicians should be familiar with the risk factors for renal disease, CIN and preventing measures.